Cerebral haemodynamics with head position changes post-ischemic stroke: A systematic review and meta-analysis. Issue 10 (October 2020) - Carvalho, Lilian B; Kramer, Sharon; Borschmann, Karen; Chambers, Brian; Thijs, Vincent; Bernhardt, Julie
The effects of upright postures on the cerebral circulation early post-ischemic stroke are not fully understood. We conducted a systematic review and meta-analysis to investigate the effects of head positioning on cerebral haemodynamics assessed by imaging methods post-ischemic stroke. Of the 21 studies included ( n = 529), 15 used transcranial Doppler. Others used near-infrared, diffuse correlation spectroscopy and nuclear medicine modalities. Most tested head positions between 0° and 45°. Seventeen studies reported changes in CBF parameters (increase at lying-flat or decrease at more upright) in the ischaemic hemisphere with position change. However, great variability was found and risk of bias was high in many studies. Pooled data of two studies ≤24 h ( n = 28) showed a mean increase in cerebral blood flow (CBF) velocity of 8.5 cm/s in the ischaemic middle cerebral artery (95%CI, −2.2–19.3) from 30° to 0°. The increase found ≤48 h ( n = 50) was of 2.3 cm/s (95%CI, −4.6–9.2), while ≤7 days ( n = 38) was of 8.4 cm/s (95%CI, 1.8–15). Few very early studies (≤2 days) tested head positions greater than 30° and were unable to provide information about the response of acute stroke patients to upright postures (sitting, standing). These postures are part of current clinical practice and knowledge on their effects on cerebral haemodynamics is required.